Antropologi Hukum dan Masyarakat Perkotaan - Warsani Warsani (Antropologi Indonesia, 1989)
The decision of Supreme Court of Justice as the formal legal system should have been strongly applied to solve legal matters such as the problem of inheritance. Among the social life of Karo, a sub-ethnic group of the Batak of North Sumatera, the national legal system which should be applied to all citizens in Indonesia, has not yet been able to be fully accepted due to the discrepancies of the nature of legal system with the nature of cultural system of the people and their customary law.